Towards a continuous adsorption process for the enrichment of ACE-inhibiting peptides from food protein hydrolysates - Hippauf, Felix; Huettner, Christiane; Lunow, Diana; Borchardt, Lars; Henle, Thomas; Kaskel, Stefan (Carbon, 2016)
Bioactive peptides such as Ile-Trp show great potential as natural ACE (angiotensin-converting-enzyme)-inhibitors. A continuous process for the up-scaled enrichment of ACE-inhibiting peptides based on a columnar adsorber system with an activated carbon stationary phase was developed. The particle size of the adsorbent and the flow rate was investigated as key factors affecting adsorption kinetics and separation performance. Batch and column adsorption experiments of model adsorbate systems were successfully transferred to a more complex system of an α-lactalbumin hydrolysate containing a multitude of species. Ile-Trp was successfully enriched from the hydrolysate by a factor of 4 using the optimized carbon column. The enrichment was more selective using smaller adsorbent particles due to improved adsorption kinetics.
CRIS-Team Scopus Importer:2023-03-20